GERAKAN PERLAWANAN GELOMBANG KEDUA DESA ADAT PASEDAHAN KABUPATEN KARANGASEM DALAM MENOLAK KEBIJAKAN REKLAMASI TELUK BENOA - Widyanata, I Made Ady; Erawan, I Ketut Putra; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2017)
ABSTRACT Benoa Bay reclamation policies led to the reaction a resistance movement of various circles of society to indigenous villages. Resistance indigenous village began to spread, which initially only indigenous coastal villages Benoa Bay, now the traditional village far from the coast of the Gulf of Benoa party to the resistance movement refuse reclamation of Benoa Bay. This research takes the traditional village Pasedahan Karangasem as a case study. The purpose of this study is to determine and describe how the resistance movement Pasedahan indigenous village in Karangasem regency refuse reclamation policy Benoa Bay. The theory used is the theory of the Resistance. The method used in this research is descriptive qualitative. Research data collection techniques by observation, interviews, literature method, discorse and documentation. This research on the findings discovered that the resistance movement is done the traditional village Pasedahan still in the form of semi-open resistance (social protests or demonstrations), installation of billboards and flags ForBALI, as well as participation in joint actions Pasubayan Village People/Pakraman. In data analyzed that there are two factors that underlie the emergence of resistance movements Pasedahan indigenous villages. First, trust/faith in the sacred area which produces resistance that there are points of sacred region Benoa Bay. Second, the sense of solidarity which produces resistance can be interpreted as a manifestation of concern society based on equality of morality, collectivity, and belief as indigenous peoples. Keywords: Social Movements Politics, Village People, Reclamation